Petiole (Rachis) Blight of Palm - Monica L. Elliott (EDIS)
In general, the “typical” or “classic” petiole blight is a disease in which the pathogen only infects the petiole. The disease symptoms may look like the pathogen has also infected the leaf blade, but this is a secondary affect from petiole infection. An exception to the “typical” petiole blight is a disease caused by Pestalotiopsis. This pathogen causes both a leaf spot and blight as well as a petiole or rachis blight, usually at the same time. It is discussed in a separate fact sheet (PP141). This document is PP-221, one of a series of the Plant Pathology Department, UF/IFAS Extension. Original publication date January 2006.